2009
DOI: 10.1159/000253551
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and 3,4-Methylenedioxymethamphetamine: Neurohormonal Aspects of Bioenergetic Stress in Ecstasy Users

Abstract: Aims: 3,4-Methylenedioxymethamphetamine (MDMA) can affect both neurotransmitter and neurohormonal activity. This review will debate the role of the metabolic activation hormone cortisol for the psychobiological effects of ecstasy/MDMA. Methods: The empirical literature on cortisol release following acute MDMA administration and cortisol functioning in drug-free recreational ecstasy/MDMA users will be reviewed. This will be followed by an overview of cortisol as a bioenergetic stress neurohormone, and a debate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 213 publications
4
84
0
Order By: Relevance
“…This is consistent with the animal literature, where high ambient temperature and other metabolic stimulants boost the acute effects of MDMA, and cause greater serotonergic neurotoxicity [21,29]. These multiple influences have been integrated within a bioenergetic stress model for recreational MDMA [24,27]. According to this model, metabolic cellular activity is increased by MDMA and other CNS stimulants.…”
Section: Andysupporting
confidence: 84%
See 2 more Smart Citations
“…This is consistent with the animal literature, where high ambient temperature and other metabolic stimulants boost the acute effects of MDMA, and cause greater serotonergic neurotoxicity [21,29]. These multiple influences have been integrated within a bioenergetic stress model for recreational MDMA [24,27]. According to this model, metabolic cellular activity is increased by MDMA and other CNS stimulants.…”
Section: Andysupporting
confidence: 84%
“…The putative role of oxytocin was debated by Gillian Broadbear in the previous paragraph. Here the energetic stress neurohormone cortisol was debated [27]. In a recent study of Ecstasy using dance clubbers, where MDMA was biochemically confirmed, an 800% increase in cortisol emerged.…”
Section: Andymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high frequency of tobacco smokers who also use ecstasy and the finding here that suggests that the use of both substances may work additively to confer greater vulnerability, more work needs to be undertaken to explore the psychobiological effects of tobacco/ecstasy co-use. For instance, in one study Ecstasy users had significantly higher cortisol levels during tobacco abstinence, than an equivalent group of abstaining smokers who were not MDMA users [7,8]. The differences between the data from the bulletin board and non-bulletin board participants reported here are intriguing and clearly warrant further investigation, including a more in-depth exploration of user characteristics from different website addresses and the complex relationship between beliefs, performance and self reports of functioning.…”
Section: Discussionmentioning
confidence: 76%
“…(MDMA) or 'Ecstasy', is a powerful sympathomimetic and metabolic stressor [1,2]. As with every other recreational stimulant, this methamphetamine derivative is associated with increased levels of psychiatric distress.…”
Section: 4-methylenedioxymethamphetaminementioning
confidence: 99%